Methionine and Choline Deficient Diet-induced Non-Alcoholic Steatohepatitis in Rats: Role of Melatonin - Mohamed M. Amin,Rania F. Ahmed,Dalia O. Saleh (Journal of Applied Pharmaceutical Science, 2017)
Objective: The present study aimed to evaluate the neuro-protective and hepato-protective activity of melatonin (MLN) on non-alcoholic steatohepatitis (NASH) in albino rats induced by methionine and choline deficient (MCD) diet. Material and Methods: To achieve this aim, rats were fed MCD diet for 8 weeks to induce non-alcoholic steatohepatitis. Oral administration of MLN (10 mg/kg/day) was done for the last two consecutive weeks. Twenty-four hours after the last dose of the MLN behavioral test, namely activity cage test was performed and the activity counts were recorded. Serum AST, ALT, ALP, GGT, total/direct bilirubin and albumin were valued to assess liver function. Moreover, hepatic interleukin-6 (IL-6) as well as nuclear factor- kβ (NF-kβ) were determined. Besides, brain biomarkers viz. ammonia, nitric oxide and brain-derived neurotrophic factor (BDNF) were measured which are reliable indices to assess brain damage. Results: MLN succeeded in suppression of NASH rats’ locomotor activity. Besides; it improved all biochemical parameters and histopathological as well as proliferating cell nuclear antigen (PCNA) immunohistochemical profiles of liver and brain. Conclusions: These results afford new intuition into the possible molecular mechanisms by which MLN faces steatohepatitis disorder, via modulation of several factors participating in the progression of this disease.
Keywords: Melatonin,Non-alcoholic steatohepatitis,methionine and choline deficient diet.